Hubungan Model Pembelajaran Kontekstual Berbasis Aktivitas Ibu Rumah Tangga terhadap Kemampuan Literasi Matematis Anak Usia Dini - Fitriani; Wiwik Novitasari; Benny Sofyan Samosir; Vitria Larseman Dela; Fatma Suryani Harahap; Husni Al Zahra; Ahyar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study was motivated by the limited use of household activities as a medium for mathematics learning for early childhood children, although daily activities have significant potential to introduce numeracy concepts in a concrete and meaningful manner. The study aimed to analyze the relationship between a contextual learning model based on housewives’ activities and the mathematical literacy skills of early childhood children in Bandar Hapinis Village. This research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The research sample consisted of 25 housewives and 25 children aged 4–6 years. Data collection was conducted through observation, and the data were analyzed using the Pearson correlation test. The findings revealed that the implementation of the contextual learning model was categorized as good, with an average observation score of 17.92. Children’s mathematical literacy skills improved from an average pretest score of 58.83 to a posttest score of 82.27. The Pearson correlation result (0.687; significance 0.000 < 0.05) indicated a positive and significant relationship between contextual learning and children’s mathematical literacy skills. However, future studies should involve larger samples and stronger research designs.